2016
DOI: 10.1016/j.yhbeh.2016.05.019
|View full text |Cite
|
Sign up to set email alerts
|

Steroid sulfatase inhibitor DU-14 protects spatial memory and synaptic plasticity from disruption by amyloid β protein in male rats

Abstract: Alzheimer's disease (AD) is an age-related mental disorder characterized by progressive loss of memory and multiple cognitive impairments. The overproduction and aggregation of Amyloid β protein (Aβ) in the brain, especially in the hippocampus, are closely involved in the memory loss in the patients with AD. Accumulating evidence indicates that the Aβ-induced imbalance of dehydroepiandrosterone (DHEA) and dehydroepiandrosterone sulfate (DHEAS) in the brain plays an important role in the AD pathogenesis and pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 57 publications
0
11
0
Order By: Relevance
“…Differential behavioral effects in the genetic and pharmacological mouse models could also be explained by complete lack of the STS protein in the deletion model versus incomplete (~70%) inhibition of the enzyme in the pharmacological model (Nicolas et al., 2001), or by deletion of additional genes or genetic elements other than Sts in the genetic model (Trent et al., 2013; Trent, Fry, Ojarikre, & Davies, 2014) and possible off‐target effects in the pharmacological model (Ho et al., 2003). There is a growing body of evidence that pharmacological manipulation of the STS axis can influence the aspects of cognition and the underlying neural substrates (Yue et al., 2016). …”
Section: Discussionmentioning
confidence: 99%
“…Differential behavioral effects in the genetic and pharmacological mouse models could also be explained by complete lack of the STS protein in the deletion model versus incomplete (~70%) inhibition of the enzyme in the pharmacological model (Nicolas et al., 2001), or by deletion of additional genes or genetic elements other than Sts in the genetic model (Trent et al., 2013; Trent, Fry, Ojarikre, & Davies, 2014) and possible off‐target effects in the pharmacological model (Ho et al., 2003). There is a growing body of evidence that pharmacological manipulation of the STS axis can influence the aspects of cognition and the underlying neural substrates (Yue et al., 2016). …”
Section: Discussionmentioning
confidence: 99%
“…Recently, an interesting in vivo study focussed on a derivative of p-O-sulphamoyl-N-alkanoyl tyramine, namely, DU-14 32 (containing an N-tetradecanoyl chain) ( Figure 6), has been described as a potential treatment method of neurodegenerative disorders (e.g. Alzheimer's disease) in rats 71 . Historically, a series of p-O-sulphamoyl-N-alkanoyl tyramines was synthesised as STS inhibitors by Li et al 72 .…”
Section: Nonsteroidal Sts Inhibitors Containing a Sulphamate Moietymentioning
confidence: 99%
“…It has been shown 74 that DU-14 can enhance the reversal of amnesia by DHEAS, suggesting that STS inhibition could promote the memory-enhancing properties of DHEAS. Yue et al 71 reported neuroprotective properties of DU-14 against neurotoxic amyloid b protein (Ab), suggesting that upregulation of endogenous DHEAS by DU-14 may be responsible for a beneficial alleviation of impairments in spatial memory and synaptic plasticity induced by Ab in rats.…”
Section: Nonsteroidal Sts Inhibitors Containing a Sulphamate Moietymentioning
confidence: 99%
“…Work in male rodents has shown that deletion of the Sts gene, or acute inhibition of the STS enzyme, is associated with numerous behavioural phenotypes including inattention, anxiety-related behaviours, aggression, perseveration, learning and enhanced memory, and behavioural inhibition (Johnson et al 2000 ; Nicolas et al 2001 ; Davies et al 2009 ; Trent et al 2012b ; Babalola et al 2012 ; Trent et al 2013 ; Davies et al 2014 ); these phenotypes may be partially related to serotonergic and cholinergic differences in the hippocampus (Trent et al 2012a ; Trent et al 2013 ; Yue et al 2016 ). In both rodents and humans, the quality of maternal behaviours is related to maternal executive function (notably offspring-related learning and memory processes, attention to relevant care cues, behavioural flexibility, and impulse regulation) mediated by cholinergic, GABAergic, and serotonergic processes (Davies 2018 ).…”
Section: Mood Abnormalities In Steroid Sulfatase–deficient Individualsmentioning
confidence: 99%